Kiai sebagai Inovator Pendidikan di Pondok Pesantren Nurud Dhalam Nyalabu Daya Pamekasan - Usman (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2023)
There have been a number of revolutionary changes occurred within the pesantren following these last three years since the new leadership of Nurud Dhalam pesantren began to take over. These include the adoption of several innovative ideas related to pesantren management as well as the improvement of formal education facilities integrated in one entity of the pesantren foundation. This research is intended to find out the role of kiai in the decision-making process of pesantren development innovation? whatever the forms of innovation Kiai introduces in the development of pesantren? and whatever the impacts of pesantren development innovation on learning activities at Pesantren Nurud Dhalam Nyalabu Daya Pamekasan are? Thus, the main purpose is to observe how and what Kiai Ach. Fauzan strive to innovate this education. Therefore, in this study, researcher will adopt the theory of social change introduced by Auguste Comte. This theory is used to measure how changes made by kiai in innovating. This type of research is descriptive qualitative field research and the data collection method utilizes triangulation method. This research found the role of Kiai Ach. Fauzan in the decision-making Process always prioritises deliberation in Pesantrens Development Innovation, including in the terms of developing the education of Pondok Pesantren Nurud Dhalam. Forms of Kiai Ach. Fauzan's Innovation towards Pesantren Development includes the establishment of formal education such as Raudlatul Athfal (RA) and Madrasah Tsanawiyah (MTs) educational institutions which previously only offered non-formal education. In addition, another form of innovation taken by pesantren is management improvement. And the results of improving the quality of education of Pondok Pesantren Nurud Dhalam are satisfaction with madrasah services and management, increasing student achievement in madrasah and the acceptance of output or graduates of Pondok Pesantren Nurud Dhalam in various best institutions in Pamekasan.